The Effect of Moringa leaf extract supplementation on IL-6 protein expression in endurance-training-induced inflammation of Wistar rat muscles - Afianti Sulastri; Natasya Natasya; Muhammad Naufal Abdurahman; Pipit Pitriani; Hamidie Ronald Daniel Ray (Universitas Pendidikan Indonesia, 2023)
Overtraining can cause muscle inflammation. Untreated inflammation might cause permanent damage. Traumas can create dysfunction physically and functionally. One study demonstrated that moringa contained a high content of micro- and macronutrients, such as protein, energy, and vitamins, and had several therapeutic effects. This study aimed to evaluate the effects of moringa in inflammation reduction, due to endurance training (eTR), on skeletal muscle. The sample consisted of 12 adults male Wistar rats separated into three groups, including two exercise groups and one non-exercise group. One of the exercise groups was given moringa leaf extract (eTMO) at a dose of 0.02 mg/kg/day of body weight, which was suspended in 0.5% Na-CMC, taken orally for 28 days. The exercise rat groups were trained on a treadmill for 30 minutes every day for 28 days. Western blotting (WB) was utilized for the detection of IL-6 protein expression. These findings demonstrated that the treatment using M. oleifera leaf extract combined with endurance exercise reduced the expression of the protein IL-6 subunit in the gastrocnemius (Gas) muscles. This data revealed that the combination of Moringa oleifera and exercise could potentially lower IL-6 levels in skeletal muscle.